Labour turnover and labour productivity in a retail organization - William Stanley Siebert; Nikolay Zubanov; Arnaud Chevalier; Tarja K. Viitanen (Institute for the Study of Labor (IZA), 2006)
We study the impact of labour turnover on labour productivity using a panel dataset of 347 shops belonging to a large UK clothing retailer over1995-1999. For the within-shop link
Keywords: 330; holding constant the shop's permanent characteristics